Construct validity for the verbal associated pairs screen. Issue 6 (18th August 2019) - Dodd, Jonathan; Murphy, Samantha; Doherty, Meghan
ABSTRACT: The present study introduces the Verbal Associated Pairs Screen (VAPS) as a new measure for assessing performance validity in pediatric populations. This study presents initial data on psychometric properties and establishes construct validity for the VAPS in a sample of 30 adolescent healthy controls and 206 youths with traumatic brain injury (TBI: moderate/severe, N = 30; mild, N = 176). The control group's age ( M = 14.93, SD = 1.8) was significantly higher than the moderate/severe TBI ( M = 13.9, SD = 2.8), t (68.508) = −3.038, p = .003, and mild TBI (mTBI) groups ( M = 14, SD = 2.8), t (54.147) = 2.038, p = .046. The TBI groups were administered the VAPS in accord with other established performance validity tests (PVTs) and well-established memory tests as part of routine clinical evaluations. The healthy control group was administered the VAPS only. VAPS score distributions for the control group were negatively skewed and highly kurtotic. VAPS scores from the moderate/severe TBI and control groups were indistinguishable for Trial 2 ( U = 274, p < .01) and the Delay ( U = 396, p = .218). In the mTBI group, convergent and divergent validity was established with other well-validated PVTs and memory tests, respectively. ROC curve analyses identified optimal cutoff scores for the VAPS Total Score, with acceptable sensitivity (55%) and excellent specificity (100%), as well as strong detectability (AUC = .829, 95% CI: 0.731 – 0.928, p < .001). Clinical applications, limitations, and directions for future research with the VAPS are discussed.